2021
DOI: 10.1016/j.envres.2021.111560
|View full text |Cite
|
Sign up to set email alerts
|

CO2 concentration monitoring inside educational buildings as a strategic tool to reduce the risk of Sars-CoV-2 airborne transmission

Abstract: In order to avoid SARS-CoV-2 transmission inside educational buildings and promote the safe reopening of schools, the Italian Government, in line with the other European countries and in accordance with the WHO recommendations, adopted a contingency plan including actions able to guarantee adequate air ventilation in classrooms. Therefore, in this pilot study, a surveillance activity based on the real-time monitoring of CO 2 levels as a proxy of SARS-CoV-2 transmission risk, was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 47 publications
4
103
0
5
Order By: Relevance
“…Measuring atmospheric CO 2 concentrations has been helpful for evaluation of the ventilation conditions in rooms of buildings aiming to decrease the transmission risk of SARS-CoV-2, which can cause COVID-19 ( Figure 3 ) [ 5 , 21 , 22 ]. Smaller droplets (<10 μm) with SARS-CoV-2 content expired from COVID-19 patients can travel tens of meters in the air while indoors and cause airborne transmission [ 23 , 24 ].…”
Section: Atmospheric Carbon Dioxide Concentrationmentioning
confidence: 99%
“…Measuring atmospheric CO 2 concentrations has been helpful for evaluation of the ventilation conditions in rooms of buildings aiming to decrease the transmission risk of SARS-CoV-2, which can cause COVID-19 ( Figure 3 ) [ 5 , 21 , 22 ]. Smaller droplets (<10 μm) with SARS-CoV-2 content expired from COVID-19 patients can travel tens of meters in the air while indoors and cause airborne transmission [ 23 , 24 ].…”
Section: Atmospheric Carbon Dioxide Concentrationmentioning
confidence: 99%
“…Whilst CO 2 levels can be used to approximate the risk of COVID-19 transmission 39 , they are only a proxy for this risk. With that caveat, some authors have suggested that CO 2 levels might be used strategically in negotiations with employers 40 . Figure 3 shows some suggested cut-off levels for denoting “low risk” (below 700 ppm), “medium risk” (700–800 ppm), “high risk” (800–1000 ppm) and “very high risk” (>1000 ppm), though other publications recommend slightly different cut-offs for these categories.…”
Section: Main Findingsmentioning
confidence: 99%
“…In this perspective, the added value of specific systems for Indoor Air Quality monitoring needs further research. Di Gilio et al (2021) , validated that CO 2 portable monitors (10 cm × 10cm) can be used to assess the potential risk of infected droplets/aerosols inhalation when CO 2 levels reach a defined threshold (fixed at 700 ppm in more recent studies) and foster the natural ventilation of the space by simply opening doors and windows for the time needed to reduce CO 2 levels. Of note, normal breathing of a child aged 7–9 years old generates 14 L of CO 2 per hour, which is 50% lower than the amount produced by a teenager, while in conditions of moderate physical activity, a 15 years old student can release up to 85 L of CO 2 per hour.…”
Section: Introductionmentioning
confidence: 98%